Do government policies drive economic growth convergence? Evidence from East Java, Indonesia - Achmad Solihin, - (Taylor and Francis Ltd., 2021)
While Indonesia has been experiencing relatively considerable and stable economic growth in the last decades, the country is prone to income disparity across regions due to uneven distribution of population, natural resources and the persistent impacts of centralized development imposed by the New Order regime. This study examines the economic growth convergence in East Java, Indonesia, from 2010 to 2019 and explores the influence of government expenditure on education, health, and capital sector on the economic growth convergence. By considering spatial dependence across regions, the result shows no strong evidence of regional income convergence in East Java. Also, this research claims the presence of spillover effect of government expenditure on education and capital sector on regional income growth. Notably, higher government expenditure of the education sector in one region could stimulate higher economic growth of its neighboring regions. Conversely, higher government expenditure on the capital sector in one region may lower the economic growth of its surrounding regions.